2016
DOI: 10.1590/0100-29452016673
|View full text |Cite
|
Sign up to set email alerts
|

PARASITISM OF FRUIT FLIES (TEPHRITIDAE) IN FIELD, AFTER THE RELEASES OF Diachasmimorpha longicaudata (ASHMEAD) (HYMENOPTERA: BRACONIDAE) IN RIO GRANDE DO SUL

Abstract: ABSTRACT-Diachasmimorpha longicaudata (ashmead) (hymenoptera: Braconidae) was introduced in 1994, in Northeastern Brazil, to evaluate its use in biological control programs of fruit flies. However, the effects of this specie on parasitism rates on the population of native parasitoids and fruit flies in Southern Brazil conditions are unknown. The objective of this study was to evaluate the impact of releases of D. longicaudata on the parasitism rates on loquats, peach trees, strawberry guava trees, and persimmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 22 publications
1
16
0
2
Order By: Relevance
“…In relation to the emergence of parasitoids and mortality, however, both had similar means, except for third instar larvae of A. fraterculus, with a higher mean number of unviable pupae and lower number of emerged parasitoids. Although C. capitata has been used for a long time in rearing of D. longicaudata in several places of the world, A. fraterculus has already been used, showing a good performance as a host (Messing et al, 1993;, Meirelles et al, 2016Harbi et al, 2018), and our study confirms this data. This aspect is important in mass rearing since studies such as those by Segura et al (2007) and Tognon et al (2013) have demonstrated that parasitoids that are reared in a given host are easier to recognize through chemical tracks, obtained by memory or learning, which would provide greater efficiency in the control of the target pest (Mattiacci & Dicke, 1995;Eben et al, 2000).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In relation to the emergence of parasitoids and mortality, however, both had similar means, except for third instar larvae of A. fraterculus, with a higher mean number of unviable pupae and lower number of emerged parasitoids. Although C. capitata has been used for a long time in rearing of D. longicaudata in several places of the world, A. fraterculus has already been used, showing a good performance as a host (Messing et al, 1993;, Meirelles et al, 2016Harbi et al, 2018), and our study confirms this data. This aspect is important in mass rearing since studies such as those by Segura et al (2007) and Tognon et al (2013) have demonstrated that parasitoids that are reared in a given host are easier to recognize through chemical tracks, obtained by memory or learning, which would provide greater efficiency in the control of the target pest (Mattiacci & Dicke, 1995;Eben et al, 2000).…”
Section: Discussionsupporting
confidence: 85%
“…As an oviposition substrate for C. capitata, a 250 ml yellow plastic tube with small perforations (FAO/IAEA/ USDA, 2003) was used. For A. fraterculus, the substrate used was a blue tissue bag covered with silicone, as described in Meirelles et al (2016). The eggs were collected daily and placed on polystyrene trays (23.5 x 18 x 1 cm), with an artificial diet based on organic carrot, beer yeast, corn flour, sugar, distilled water, sodium benzoate (Dinâmica ® ), nipagin (Synth ® ) and citric acid (Synth ® ) (modified from Terán, 1977).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diachasmimorpha longicaudata (Ashmead) (Hymenoptera: Braconidae), tem sido o agente mais utilizado em programas de controle de moscas-das-frutas (González et al, 2007;López et al, 2009;Meirelles et al, 2016;Vargas et al, 2016). Este inseto é um endoparasitoide coinobionte que oviposita no último ínstar larval de tefritídeos e completa o desenvolvimento no estágio pupal do hospedeiro (Carvalho & Nascimento, 2002).…”
unclassified
“…A essência de baunilha foi utilizada por este odor não fazer parte do contexto ecológico do parasitoide e serviu como "odor modelo" também utilizado por outros autores (Takasu & Lewis, 1996;Tognon et al, 2013;Gregório et al, 2015). O óleo de laranja foi escolhido por apresentar ação repelente para outros insetos inclusive D. longicaudata (bioensaios piloto), objetivando observar uma possível reversão de comportamento para este parasitoide Meirelles et al (2016). Diariamente os ovos eram retirados e colocados sobre voile azul (3 cm²), em placas de Petri (9 × 2 cm), contendo papel filtro umedecido no fundo, acondicionadas durante 48 h em câmara climatizada.…”
unclassified